Common Variation in EDN1 Regulatory Regions Highlights the Role of PPARγ as a Key Regulator of Endothelin in vitro - Lago-Docampo, Mauro; Solarat, Carlos; Méndez-Martínez, Luis; Baloira, Adolfo; Valverde, Diana (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary Arterial Hypertension (PAH) is a rare disease caused by the obliteration of the pulmonary arterioles, increasing pulmonary vascular resistance and eventually causing right heart failure. Endothelin-1 (EDN1) is a vasoconstrictor peptide whose levels are indicators of disease progression and its pathway is one of the most common targeted by current treatments. We sequenced the EDN1 untranslated regions of a small subset of patients with PAH, predicted the effect in silico, and used a luciferase assay with the different genotypes to analyze its influence on gene expression. Finally, we used siRNAs against the major transcription factors (TFs) predicted for these regions [peroxisome proliferator-activated receptor γ (PPARγ), Krüppel-Like Factor 4 (KLF4), and vitamin D receptor (VDR)] to assess EDN1 expression in cell culture and validate the binding sites. First, we detected a single nucleotide polymorphism (SNP) in the 5' untranslated region (UTR; rs397751713) and another in the 3'regulatory region (rs2859338) that altered luciferase activity in vitro depending on their genotype. We determined in silico that KLF4/PPARγ could bind to the rs397751713 and VDR to rs2859338. By using siRNAs and luciferase assays, we determined that PPARγ binds differentially to rs397751713. PPARγ and VDR Knock-Down (KD) increased the EDN1 mRNA levels and EDN1 production in porcine aortic endothelial cells (PAECs), while PPARγ and KLF4 KD increased the EDN1 production in HeLa. In conclusion, common variants in EDN1 regulatory regions could alter EDN1 levels. We were able to validate that PPARγ binds in rs397751713 and is a key regulator of EDN1. In addition, KLF4 and VDR regulate EDN1 production in a cell-dependent manner, but VDR does not bind directly to the regions we studied.